Role of Restorativeness in Improving the Psychological Well-Being of University Students - Yusli, Nurul Ain Nabilla Mohd; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Ghiami, Zeinab; Ahmad, Noorlila (Frontiers in Psychology, 2021)
Many university students experience high levels of study-related fatigue, necessitating opportunities for restoration. They would benefit from campus-based physical activities, which would provide effective restoration breaks and allow them to return to their studies cognitively refreshed. Thus, a cross-sectional study was conducted to assess the association between perceived restorativeness among postgraduates and their psychological well-being by using four constructs of Kaplan’s attention restoration theory (ART): fascination, being away, extent, and compatibility. In this study, nature view windows were also used as a moderator. Malaysian postgraduate students [n = 192; 94 females; age in years (M = 30.64, SD = 2.73)] completed Ryff’s scale of psychological well-being (PWB) and perceived restorativeness scale (PRAS). This study used the partial least squares-structural equation model (PLS-SEM) to examine these relationships. The results showed that three ART facets, namely being away, fascination, and compatibility, were significant predictors of psychological well-being across the total sample size. Furthermore, for the participants residing in university dormitories, windows overlooking nature enhanced the relationships between being away, compatibility and fascination, and psychological well-being than those with less natural views. Thus, this study has confirmed the moderating effect of the nature view window, providing insights into the ART constructs that facilitate and enhance restorative experiences. By strengthening ART with additional factors, this study contributes towards the improvement of university students’ psychological well-being.